Photoactive Hybrid Gelators Based on a Luminescent Inorganic [Cu4I4] Cluster Core. Issue 47 (21st October 2013) - Benito, Quentin; Fargues, Alexandre; Garcia, Alain; Maron, Sébastien; Gacoin, Thierry; Boilot, Jean‐Pierre; Perruchas, Sandrine; Camerel, Franck
<x xml:space="preserve">Abstract</x> Luminescent clustogelator: Hybrid gelators with a [Cu4I4] cluster core functionalized by cholesteryl derivatives allow solvent gelation through the formation of a globular network (see figure). The resulting gels display thermochromic and rigidochromic luminescence properties, the latter being used to probe the dynamics of the gelation phenomenon.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>